Evolución y estructura psicolingüística de la función poética del lenguaje. - Gonzales Moreyra, Raúl (1988)
Cloze technique was used to examine the reading of poetry in 200 children aged 7 through 16. Performance was scored according to Jakobson and Levin criteria. Results demonstrate the developmental nature of this function and its correspondent to Piaget's concrete and formal-operational stages.